2021
DOI: 10.3389/fneur.2021.678924
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Cognitive Impairment in Individuals With Mild and Moderate COVID-19: A Case Series

Abstract: Background: Previous reported neurologic sequelae associated with SARS-CoV-2 infection have mainly been confined to hospital-based patients in which viral detection was restricted to nasal/throat swabs or to IgM/IgG peripheral blood serology. Here we describe seven cases from Brazil of outpatients with previous mild or moderate COVID-19 who developed subacute cognitive disturbances.Methods: From June 1 to August 15, 2020, seven individuals 18 to 60 years old, with confirmed mild/moderate COVID-19 and findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The mean age of participants ranged from 42.57 ± 7.23 ( Matos et al, 2021 ) to 79 ± 8 ( Pirker-Kees et al, 2021 ), yet in the majority of studies, the mean age was 60 ( Supplementary Material, Fig. F2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of participants ranged from 42.57 ± 7.23 ( Matos et al, 2021 ) to 79 ± 8 ( Pirker-Kees et al, 2021 ), yet in the majority of studies, the mean age was 60 ( Supplementary Material, Fig. F2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The FAB global score was also impaired in the third study ( Versace et al, 2021 ), reporting that 12/12 non-ICU-admitted subjects performed under the normality cutoff. Finally, one study reported 5/7 subjects with mild COVID-19 performing under the normality cutoff (mean and SD: 5 ± 2.94; max score: 10; cutoff: 9) during the clock drawing test ( Matos et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, comparison is difficult as they used a screening test and did not define cognitive impairment (Del Brutto et al, 2021). A case series study of seven mild-to-moderate cases indicated 100% impairment based on screening tests (Matos et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, comparison is difficult as they used a screening test and did not define cognitive impairment ( Del Brutto et al, 2021 ). A case series study of seven mild-to-moderate cases indicated 100% impairment based on screening tests ( Matos et al, 2021 ). Further research is needed to determine the incidence and characteristics of cognitive impairment in non-critical COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…which is similar to the findings of the present study. This is especially pertinent given that anxiety has consistently been identified as a key predictor of neurocognitive disorders in several meta-analyses [4,8,10] more than seven days after the onset of the disease [27].…”
Section: Resultsmentioning
confidence: 99%